STRENGTHENING IMPLEMENTATION 5S WORK CULTURE TO FINANCIAL PERFORMANCE AND PRODUCTIVITY AT PT PETROKIMIA GRESIK - Windy Frecelia Putri; Sriyono; Wisnu Panggah Setiyono (Universitas Airlangga, 2023)
Introduction: The preliminary, applying Japanese housekeeping, namely the 5S such as Seiri, Seiton, Seiso, Seiketsu, and Shitsuke, is one way to achieve these five qualities. 5S is a procedure that controls and standardizes the workplace by ensuring the efficiency of business processes to provide a safe and high-quality workplace. Aims: This research was a case study that aimed to observe how the 5S was implemented as a work culture and how it influenced organizational performance. Method The research was qualitative research using an ethnography approach through the description of the data collected through field observation. The data analysis included data reduction, data presentation, and drawing conclusions. It was found by observing indicators that activities that needed development were found, such as: Sort Out = 4, Set in Order = 1, Sweep = 1, Standardize = 2 and Sustain = 1. Results Findings show that the previously unfavorable working conditions of employees have now improved and can be further improved by implementing 5Ss. The results show that if the subsidiary has an increase in financial performance, it can be seen from the overall average value of Assets = 0.00103 and the GPM value = 0.547 is higher than before. Conclusion Increased work efficiency and effectiveness are well-coordinated and work quality and safety are well-maintained. Then the financial performance changed greatly, which initially declined due to the weakness of the 5S work culture, has now drastically improved thanks to the 5S work culture that was successfully strengthened.